2021
DOI: 10.1016/j.heliyon.2021.e06785
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that hematopoietic stem cells in human umbilical cord blood is infectable by dengue virus: proposing a vertical transmission candidate

Abstract: Background Recent studies have shown that dengue virus (DENV) can efficiently infect bone marrow hematopoietic stem cells (HSCs) as well as the placenta of pregnant women. Although mother-to-infant vertical transmission of DENV through the placenta has been well documented, the evidence of cell-associated vertical transmission is still unknown. Whether DENV can infect umbilical cord blood (UCB) cells before reaching the fetus remains to be explored. Here, we proposed that human UCB cells were perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
(43 reference statements)
0
2
0
Order By: Relevance
“… 121 CD44 is an early marker of differentiation for these immature CD34 + cells. 122 Studies have shown that cells with higher CD44 expression levels have better proliferation and differentiation capabilities into AT1 cells. 93 Therefore, the study of HSCs with a general expression of CD34 and CD44 markers could provide insight into the development of lung fibrosis.…”
Section: Stem Cells: a Potential Avenue For Treatment Of Pulmonary Fi...mentioning
confidence: 99%
“… 121 CD44 is an early marker of differentiation for these immature CD34 + cells. 122 Studies have shown that cells with higher CD44 expression levels have better proliferation and differentiation capabilities into AT1 cells. 93 Therefore, the study of HSCs with a general expression of CD34 and CD44 markers could provide insight into the development of lung fibrosis.…”
Section: Stem Cells: a Potential Avenue For Treatment Of Pulmonary Fi...mentioning
confidence: 99%
“…Previous evidence of DENV and CHIKV outbreaks has demonstrated that pregnant women are at high risk of experiencing pregnancy complications during viral infection [ 52 , 75 , 76 , 77 , 78 ]. In addition, there are some reports of the vertical transmission of these microorganisms, raising awareness of the importance of better understanding the role of the placenta in DENV and CHIKV infections [ 79 , 80 , 81 ]. Established in the third week of gestation, the placenta is characterized as a temporary and chimerical organ, formed by maternal and fetal tissue, that plays an essential role in the development and support of pregnancy.…”
Section: The Placentamentioning
confidence: 99%